Interactive Plan Selection Using Linear Temporal Logic, Disjunctive Action Landmarks, and Natural Language Instruction - Chakraborti, Tathagata; Kang, Jungkoo; Fuggitti, Francesco; Katz, Michael; Sohrabi, Shirin (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
We present Lemming – a visualization tool for the interactive selection of plans for a given problem, allowing the user to efficiently whittle down the set of plans and select their plan(s) of choice. We demonstrate four different user experiences for this process, three of them based on the principle of using disjunctive action landmarks as guidance to cut down the set of choice points for the user, and one on the use of linear temporal logic (LTL) to impart additional constraints into the plan set using natural language (NL) instruction.